Continuum resonances with shielded Coulomb-like potential and Efimov effect - Tusnski, D. S. [UNESP]; Yamashita, Marcelo Takeshi [UNESP]; Frederico, T.; Tomio, L. [UNESP] (Springer, 2014)
Motivated by the possibility of the second energy level (0 (2) (+) ) of C-12 (in a three-alpha model) to turn into an Efimov state, we study a simple non-realistic toy model formed by three bosons interacting by the phenomenological s-wave Ali-Bodmer potential plus a Coulomb interaction. An artificial three-body potential was used to create a resonance with energy close to the energy of the 0 (2) (+) of C-12, 0.38 MeV. The strength of the Coulomb potential is decreased until the energies of the two alpha pairs are zero. The system was placed inside a harmonic trap and a stabilization method has been used to calculate the energies of the resonances. We found that the shielded-Coulomb potential, which keeps the long tail, is not able to produce the Efimov effect. The energy of the three alphas decreases only to 0.19 MeV when the two-body energy crosses the threshold to become bound.